THE TRANSFORMATION OF EU ENLARGEMENT POLICY: IN SEARCH OF THE THIRD WAY - Kasčiūnas, Laurynas (Politologija, 2015)
The principle “pace follows quality” is gaining increasing importance in further EU enlargement. Exactly because of its increasing importance enlargement process is likely to experience a slow-down and perhaps a temporary suspension. One of the main arguments for such a suspension is inability of EU to deal with political, economic and administrational challenges that the previous and future enlargements inevitably pose. According to classical logic of the “enlargement versus deepening” dilemma it might be stated that further enlargement without proper consideration of EU capabilities to embrace new members and of their internal level of adoption of EU rules of the game pose a threat of internal crisis to EU-expanded.Stagnation of EU enlargement implicates that policy alternatives to enlargement and various models of integration without membership become essential. Obviously it is the “third way” (development of integration models that do not grant formal membership) that is expected to resolve the “enlargement versus deepening” dilemma. Various models that pursue integration with EU without awarding formal membership are an embodiment of attempts to solve EU absorption capacity problems. This applies to a variety of special relationships that envisage participation of third countries in EU internal market, ease of visa regime and etc. Nevertheless, it remains unclear if such models of integration should be considered as an interim stage on the way to membership or a sort of external europeanization that intends to distinguish among those who have an EU prospect and those who will never have one.Authors dealing with issues of external europeanization often conclude that models of integration without membership rely heavily on methods similar to enlargement methods. This applies especially to European Neighborhood Policy that intends to solve problems of inclusion/exclusion and involvement/security of the third countries. It is recognized, however, that alternatives to enlargement lack an essential mechanism, an incentive that would induce reform and approximation to European standards, i. e. these models do not provide a membership opportunity. Thus principle of conditionality that lies at the heart of such models fails without proper incentives to reform. Therefore a vicious circle emerges: with no membership opportunity there is no reform incentive and lack of reform hinders the possibility to transpose cooperation with EU to a qualitatively upper political, economic and institutional level. That raises a question if the enlargement “toolkit” (conditionality principle first of all) may fruitfully function in models of integration without membership.Theory of europeanization proposes that internal EU integration produces certain modes of governance and regulation that are in turn transferred to third states through instruments of europeanization. This means that with deepening of EU integration (in a mode of positive integration) costs of compliance with the European rules mount for third countries heavily. Thus as positive integration increases in EU, a protectionist/adaptation barrier arises towards third countries. Principle of conditionality that does not imply membership possibility turns into a simulacra of enlargement: the adoption pressure increases although incentives to its acceptance are absent.